Exploiting arginine distributions for the selective and efficient depletion of arginine-rich plasma proteins. Issue 82 (15th September 2020) - Hu, Xue; Wang, Jian-Hua; Chen, Xu-Wei
Abstract : The distribution of arginine residues in protein chains provides a new basis for the efficient capturing of arginine-rich proteins from complex matrices. Abstract : The number and arrangement of arginine (Arg) residues in protein chains contribute greatly to the selective capturing of proteins on a designed adsorbent consisting of organic phosphate functionalized fibrous SiO2 microspheres, and the efficient depletion of high abundance Arg-rich protein species from human plasma is achieved.